2022
DOI: 10.1111/jfpe.13996
|View full text |Cite
|
Sign up to set email alerts
|

Potentials of3Dextrusion‐based printing in resolving food processing challenges: A perspective review

Abstract: Three‐dimensional (3D) printing has promising application potentials in improving food product manufacturing, increasingly helping in simplifying the supply chain, as well as expanding the utilization of food materials. To further understand the current situation of 3D food printing in providing food engineering solutions with customized design, the authors checked recently conducted reviews and considered the extrusion‐based type to deserve additional literature synthesis. In this perspective review, therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(6 citation statements)
references
References 98 publications
0
1
0
Order By: Relevance
“…manufacturers and academia for its potential to customize food products according to necessities and preferences. Currently, 3D printing techniques available in food production mainly include extrusion-based printing (or fused deposition modelling), selective sintering printing, binder jetting, and inkjet printing [102][103][104][105]. Among them, extrusion-based printing is the most widely used in the food sector due to the multiple choices of printed materials and simple operation of the printing system [106].…”
Section: Designing Food Texture With 3d Printingmentioning
confidence: 99%
“…manufacturers and academia for its potential to customize food products according to necessities and preferences. Currently, 3D printing techniques available in food production mainly include extrusion-based printing (or fused deposition modelling), selective sintering printing, binder jetting, and inkjet printing [102][103][104][105]. Among them, extrusion-based printing is the most widely used in the food sector due to the multiple choices of printed materials and simple operation of the printing system [106].…”
Section: Designing Food Texture With 3d Printingmentioning
confidence: 99%
“…3D food printers typically contain small parts and tubes that may hinder thorough cleaning, which may lead to microbial buildup within the printer (Agunbiade et al., 2022). For instance, it was found that high levels of bacterial and yeast contamination (4–5 log CFU/g) in 3D printed foods made from blended fruits and vegetables even though all ingredients were washed thoroughly prior to the 3D printing process (Severini, Derossi et al., 2018).…”
Section: Nfps Food Safety Considerationsmentioning
confidence: 99%
“…In particular, potato starch, unlike other starches, exhibits a low gelatinization temperature and enhanced water absorption due to the covalently bound phosphate group in amylopectin [ 27 ]. These characteristics contribute to stabilizing physical properties and maintaining the shape of the final product [ 28 , 29 ]. However, the gelatinization of starch can potentially rapidly clog the nozzle.…”
Section: Introductionmentioning
confidence: 99%